Isolation and characterization of Brochothrix phage ADU4 - Abdulkerim Karaynir; Hanife Salih; Bülent Bozdoğan; Özgür Güçlü; Dilek Keskin (Virus Research, 2022)
B. thermosphacta is a psychrotrophic bacterium that often forms the predominant part of the spoilage microflora of aerobically and anaerobically stored meats. Bacteriophages are natural enemies of bacteria and their potential for use in environmentally friendly biocontrol of specific pathogens in food is being intensively studied. In this study, we reported the isolation and characterization of the newly isolated lytic Brochothrix phage ADU4, which is capable of infecting the B. thermosphacta bacterium. For the characterization of Brochothrix phage ADU4; host range, multiplicity of infection values (MOI), phage growth parameters (latent period and burst size), stability at various temperatures and pH, reduction growth of bacteria, effect on biofilm, and molecular characterization were investigated. The spot-test analysis showed positivity with B. thermosphacta strains, while no infection was observed in any other species and genera of bacteria tested. The optimal MOI value of the phage was determined as 0.1. The phage latent period and burst sizes were 40–50 min and 311 PFU/ml per infected host cell, respectively by one-step growth curve analysis. Brochothrix phage ADU4 reduced bacteria immediately after infection, which is shown by optical density (OD) measurement and colony counting (<10 CFU/ml) for 3 days. The degradation of B. thermosphacta in biofilm by Brochothrix phage ADU4 was analyzed and it was found that high titer phage breakdown the existing biofilm and also persistently inhibited biofilm formation. Brochothrix phage ADU4 genome was found to be 127,819 bp, and GC content 41.65%. The genome contains 217 putative open reading frames (ORFs), 4 tRNAs, and additionally, no known virulence and antibiotic resistance genes (AMR) were identified. Brochothrix phage ADU4 showed a high identity (96.09%) to the A9 phage that belongs to the Herelleviridae family. Nevertheless, the assembly module and its around appeared less conserved, and some DNA fragments in Brochothrix phage ADU4 genome were not found in A9 genome and vice versa. A9 contains TnpB, a transposase accessory protein involved in lysogenicity which is absent in Brochothrix phage ADU4. In contrary Brochothrix phage ADU4 had auxiliary metabolic genes (AMG) mostly carried by lytic phages. All these results showed that the Brochothrix phage ADU4 has excellent properties such as strong antibacterial activity, short latent period, high burst size, stability in different conditions, inhibition of biofilms, and absence of virulence and AMR genes. Based on all these features, this newly isolated phage is promising to control B. thermosphacta contamination in meat and meat products, and has the potential to be used alone or in combination with phage cocktails.